Number of Childbearing Partners, Status, and the Fertility of Men and Women in the U.S. - Hopcroft, Rosemary L. (Frontiers in Sociology, 2018)
Theory from evolutionary biology suggests that status and access to resources will influence the number of mating partners somewhat differently for men and women, yet little previous research has examined the relationship between status and number of child bearing partners for men and women in the U.S. This paper uses newly available data on a large probability sample of the U.S. population (the Study of Income and Program Participation) to evaluate the relationship between number of child bearing partners, socioeconomic status, and subsequent fertility for men and women in the U.S. Results show that education (net of income and net worth) is always negatively related to the number of child bearing unions and fertility for both men and women. For men, personal income and personal net worth are positive predictors of both number of child bearing partners and fertility, while for women personal income and personal net worth are negative predictors of number of child bearing partners and fertility. For men, the positive effect of income on number of child bearing partners is because low income men are more likely to have no child bearing partners at all and not because high income men are more likely to have multiple partners. Men with higher net worth do have more child bearing partners than other men, all else being equal. Both men and women who have a larger number of child bearing partners do have more children, all else being equal, although this effect is stronger for men than for women. Of those with multiple child bearing unions, men and women with both very high and very low incomes have more children than those with middle incomes.